Time-dependent behaviour prediction of the prestressed HPC I-girder. (15th December 2019) - Gedam, Banti A.
Highlights: An incremental time-step analysis method have been adopted to predict time-dependent behaviour of HPC prestresed I-girder. Experimental study on HPC material properties, i.e., shrinkage and creep have been performed. Effect of supplementary cementitious materials on HPC has been studied. A comparative appraisal of existing material models with experimental database of HPC have been done. Abstract: A time-dependent behaviour prediction of the prestressed concrete I-girder made from high-performance concrete (HPC) is very difficult. Overestimation or underestimation of the deflection (camber) and prestress loss may be affecting their service life and even also a failure. In this study, time-dependent behaviour of the prestressed I-girder was predicted using experimentally measured material properties data of HPC, i.e., shrinkage, creep and modulus of elasticity. Four independent HPC mixes of M50 grade concrete were designed as per IS 10262 and considered as a reference mixes to study its influence on the time-dependent behaviour of prestressed I-girder. HPC Mix-I, was prepared only using ordinary Portland cement (OPC) while others Mix-II, Mix-III, and Mix-IV were prepared using OPC as the main binder with the addition of one supplementary cementitious material (SCM), i.e., fly ash (FA), silica fume (SF) and ground granulated blast-furnace slag (GGBS). A validated incremental time-step analysis method was adopted to predict deflections, fibre stresses and prestress losses up to 1106 days (3 years) of prestressed I-girder. A predicted time-dependent behaviour is a good agreement with field measured data when the analysis method is used experimentally measured properties of concrete. A comparative appraisal using estimated material properties from the existing material models (i.e., ACI, FIB, B3, GL, and ANN) with experimental test data has also been done to find their reliability for HPC prestressed I-girder. A time-step analysis method can provide an accurate prediction of the time-dependent behaviour of HPC prestressed I-girder, if the measured material properties considered as an input parameter.